The impact of COVID-19 on people who inject drugs in New York City: increased risk and decreased access to services - Yesenia Aponte-Melendez; Pedro Mateu-Gelabert; Chunki Fong; Benjamin Eckhardt; Shashi Kapadia; Kristen Marks (BMC, 2021)
Abstract Background While people who inject drugs (PWID) are vulnerable to the adverse outcomes of events like COVID-19, little is known regarding the impact of the current pandemic on PWID. We examine how COVID-19 has affected PWID in New York City across four domains: substance use, risk behaviors, mental health, and service utilization. Methods As part of a randomized trial to improve access to HCV treatment for PWID, we recruited 165 participants. Eligibility criteria included detectable HCV RNA and recent drug injection. The present cross-sectional analysis is based on a subsample of 106 participants. We compared responses between two separate samples: 60 participants interviewed prior to the pandemic (pre-COVID-19 sample) and 46 participants interviewed during the pandemic (COVID-19 sample). We also assessed differences by study group [accessible care (AC) and usual care (UC)]. Results Compared to the pre-COVID-19 sample, those interviewed during COVID-19 reported higher levels of mental health issues, syringe reuse, and alcohol consumption and greater reductions in syringe-service programs and buprenorphine utilization. In the analysis conducted by study group, the UC group reported significantly higher injection risk behaviors and lower access to buprenorphine treatment during COVID-19, while during the same period, the AC group reported lower levels of substance use and injection risk behaviors. Conclusion The current study provides insight on how COVID-19 has negatively affected PWID. Placing dispensing machines of harm-reduction supplies in communities where PWID live and increasing secondary exchange, mobile services, and mail delivery of supplies may help maintain access to lifesaving supplies during big events, such as COVID-19. Trial registration ClinicalTrials.gov NCT03214679. Registered July 11 2017. https://clinicaltrials.gov/ct2/show/NCT03214679 .